H-bonding directed formation of 1D-single chains, 2D-sheets, and 3D structures in magnetically coupled tetranuclear nickel(II) complexes with incomplete double cubane core. (17th February 2017) - Tandon, Santokh S.; Bunge, Scott D.; Patel, Neil; Sanchiz, Joaquin
Graphical abstract: Synthesis, structures, and magnetism of ferromagnetically coupled tetranickel (Ni4 ) complexes of three new Schiff base ligands: [Ni4 (H2 L −1 )2 (μ-CH3 CO2 )2 (μ3 -1, 1, 1-N3 )2 (μ-1, 1-N3 )2 ]·2CH3 OH (1 ), [Ni4 (H2 L −1 )2 (μ2 -1, 1-N3 )2 (N3 )2 (μ3 -OCH3 )2 (H2 O)2 ] (2 ), [Ni4 (H2 L −1 )2 (μ3 -1, 1, 1-N3 )2 (μ-1, 1 -N3 )2 (CH3 OH)2 (Cl)2 ]·4CH3 OH (3 ), [Ni4 (H4 L1 −1 )2 (μ3 -1, 1, 1-N3 )2 (μ-1, 1-N3 )2 (CH3 OH)2 (OH)2 ]·2H2 O (4 ), and [Ni4 (HL2 −2 )2 (APD −1 )2 ][ClO4 ]2 ·2H2 O·2CH3 OH (5 ) are reported which grow into fascinating 2D-sheets, (1, 2, and4 ), 1D-single chains (3 ), and 3D (5 ) structures through a symmetrical network of H-bonding. Abstract: Reactions of 2, 6-diformyl-4-methylphenol (DFMF) with 1-amino-2-propanol (AP) and 2-amino-1, 3-propanediol (APD) in the presence of nickel(II) salts, NiX2 (X = CH3 CO2 −, NO3 −, Cl −, ClO4 −, BF4 − )/sodium azide (NaN3 ), and triethylamine (TEA), in one pot self-assemble giving tetranuclear coordination complexes of nickel(II) with an incomplete double cubane structural core: [Ni4 (H2 L −1 )2 (μ-CH3 CO2 )2 (μ3 -X)2 (μ-1, 1-N3 )2 ]·2CH3 OH X = 1, 1, 1-N3 (1A ) and OCH3 (1B ), [Ni4 (H2 L −1 )2 (μ-1, 1-N3 )2 (N3 )2 (μ3 -OCH3 )2 (H2 O)2 ] (2 ), [Ni4 (H2 L −1 )2 (μ3 -1, 1, 1-N3 )2 (μ-1, 1-N3 )2 (CH3 OH)2 Cl2 ]·4CH3 OH (3 ), [Ni4 (H4 L1 −1 )2 (μ3 -1, 1, 1-N3 )2 (μ-1, 1-N3 )2 (CH3 OH)2 (OH)2 ]·2H2 O (4 ), and [Ni4 (HL2 −2 )2 (APD −1 )2 ][ClO4 ]2 ·2H2 O·2CH3 OH (5 ). In1 –3, H2 L −1, in4, H4 L1 −1, and in5, HL2 2− represent a singly deprotonated chiral, potentially pentadentate trianionic double Schiff base ligand, H3 L; a singly deprotonated potentially heptadentate pentaanionic double Schiff base ligand, H5 L1; and a doubly deprotonated potentially tetradentate trianionic single Schiff base ligand, H3 L2 respectively. In1A, 3, and4 two dinickel (Ni2 ) units are connected through two doubly bridging end-on (EO) μ-azido and two triply bridging EO μ3 -azido bridges and in2, though two EO μ-azido and two μ3 -1, 1, 1-methoxy bridges generating tetranuclear units. In each dinuclear unit two nickel centers are bridged through one μ-phenolate oxygen from H2 L −1, one μ-CH3 CO2 −, and one EO μ3 -azido nitrogen (1 ) and through one μ-phenolate oxygen from H2 L −1 /H4 L1 −1 and one μ3 -methoxy oxygen (2 )/one μ3 -azido nitrogen (3 and4) . In5, two nickel(II) ions in the dinuclear unit are bridged though phenoxide oxygen and alkoxide oxygen bridges and two dinuclear units are interconnected via six symmetry related alkoxide bridges forming tetranickel units. In1 –4 neutral tetranuclear [Ni4 ] units and in5, cationic tetranickel [Ni4 ] 2+ units are interconnected by a symmetrical network of H-bonding between coordinated/uncoordinated hydroxido groups in the side arms of the double Schiff-base ligands, coordinated hydroxide ion/chloride ion, and uncoordinated methanol/water molecules producing H-bonding stabilized 2D-sheet structures (1, 2, 4 ), a 1D-single chains (3), and a 3D structure (5 ). Bulk magnetization measurements on1 –4 demonstrate that the magnetic interactions are completely dominated by an overall ferromagnetic coupling occurring between Ni(II) ions with coupling constants ( J 1, J 2, and J 3 ) ranging from 13.19 to 22.10, (−9.05) to (1.74), and 14.79 to 25.59 cm −1 respectively (in the H ̂ = - 2 J 1 ( S ̂ 1 S ̂ 3 + S ̂ 2 S ̂ 4 ) - 2 J 2 ( S ̂ 1 S ̂ 4 + S ̂ 2 S ̂ 3 ) - 2 J 3 ( S ̂ 1 S ̂ 2 ) + D ( S ̂ Z 1 2 + S ̂ Z 2 2 + S ̂ Z 3 2 + S ̂ Z 4 2 ) expression).